The Transgressor's Response to Denied Forgiveness. Issue 1 (March 2016) - Jennings, David J.; Worthington, Everett L.; Van Tongeren, Daryl R.; Hook, Joshua N.; Davis, Don E.; Gartner, Aubrey L.; Greer, Chelsea L.; Mosher, David K.
The study of forgiveness has flourished in recent years, but little is known about how transgressors respond when their request for forgiveness is denied. Two studies examined how transgressors react to a denied request for forgiveness in romantic relationships. Across both studies, when participants were denied forgiveness or delayed in receiving a forgiving response, they exhibited differences in the degree to which they held unforgiving motivations (e.g., anger and avoidance) and experienced positive emotions (e.g., empathy). The observed effects remained even after controlling for relationship commitment in Study 2. These results expand our knowledge of forgiveness processes by describing in more detail the internal experience and motivations of the transgressor toward the victim when forgiveness is denied, which has implications for relational repair (e.g., transgressor's motivations toward re-engaging and repairing the relationship) after an offense has occurred in romantic relationships.